1990
DOI: 10.1002/jmor.1052060311
|View full text |Cite
|
Sign up to set email alerts
|

Comparative ultrastructure of ant spermatozoa (formicidae: Hymenoptera)

Abstract: Mature spermatozoa from spermathecae of founding queens were obtained from 5 species of ants, representing the major subfamilies Myrmicinae (Acromyrmex versicolor, Crematogaster sp.) and Dolichoderinae (Tapinoma sessile, Conomyrma insana, Conomyrma wheeleri). The ultrastructure of ant spermatozoa has many features in common with that of higher insects and is similar to that of other Hymenoptera. Structural similarities to spermatozoa of other Hymenoptera include an acrosome containing an internal rod that exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 16 publications
2
46
0
Order By: Relevance
“…The asymmetry in length and diameter of these structures is a characteristic shared by all Apoidea (e.g. Zama et al, 2001, Zama et al, 2004, Zama et al, 2005c, Báo et al, 2004, Fiorillo et al, 2005aand Fiorillo et al, 2005b and Vespidae ( Mancini et al, 2006), while symmetry has been previously reported for Formicidae ( Wheeler et al, 1990, Lino-Neto et al, 2000band Mancini et al, 2005. These patterns seem to be homoplastic, because large variations are found within the Hymenoptera: they are asymmetric in some Symphyta ( Newman and Quicke, 1999a), Eucoilidae ( Newman and Quicke, 1999b) and Megalyroidea ( Newman and Quicke, 2000), while in Siricoidea (Symphyta) ( Newman and Quicke, 1999a), Ichneumonoidea ( Quicke et al, 1992) and Chalcidoidea ( Lino-Neto et al, 1999, Lino-Neto et al, 2000aand Lino-Neto and Dolder, 2001b they are symmetric.…”
Section: Linomentioning
confidence: 84%
See 3 more Smart Citations
“…The asymmetry in length and diameter of these structures is a characteristic shared by all Apoidea (e.g. Zama et al, 2001, Zama et al, 2004, Zama et al, 2005c, Báo et al, 2004, Fiorillo et al, 2005aand Fiorillo et al, 2005b and Vespidae ( Mancini et al, 2006), while symmetry has been previously reported for Formicidae ( Wheeler et al, 1990, Lino-Neto et al, 2000band Mancini et al, 2005. These patterns seem to be homoplastic, because large variations are found within the Hymenoptera: they are asymmetric in some Symphyta ( Newman and Quicke, 1999a), Eucoilidae ( Newman and Quicke, 1999b) and Megalyroidea ( Newman and Quicke, 2000), while in Siricoidea (Symphyta) ( Newman and Quicke, 1999a), Ichneumonoidea ( Quicke et al, 1992) and Chalcidoidea ( Lino-Neto et al, 1999, Lino-Neto et al, 2000aand Lino-Neto and Dolder, 2001b they are symmetric.…”
Section: Linomentioning
confidence: 84%
“…This nuclear insertion is displaced to one side (asymmetric) as we also observed in Microstigmus. Despite these exceptions, the acrosome in Hymenoptera is made up of an acrosomal vesicle and a perforatorium (bilayered pattern) ( Cruz-Höfling et al, 1970, Wheeler et al, 1990, Quicke et al, 1992, Newman and Quicke, 1999a, Lino-Neto and Dolder, 2001a, Lino-Neto and Dolder, 2002, Zama et al, 2001, Zama et al, 2004, Zama et al, 2005c, Báo et al, 2004, Badke et al, 2005, Fiorillo et al, 2005a, Fiorillo et al, 2005band Mancini et al, 2006 or includes an additional third layer, an extracellular sheath, which covers all the acrosomal vesicle and part of the nucleus ( Quicke et al, 1992, Newman and Quicke, 1998, Newman and Quicke, 1999b, Lino-Neto et al, 1999, Lino-Neto et al, 2000aand Lino-Neto and Dolder, 2001a. As a rule, the perforatorium is dense and compact, but in some bees ( Báo et al, 2004, Fiorillo et al, 2005a and in the Vespidae Agelaia vicina ( Mancini et al, 2006), it appears slightly paracrystalline.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was described for Symphyta (Quicke et al, 1992 andQuicke, 1999a), parasitic wasps (Lino-Neto and Dolder, 2001a), ants (Wheeler et al, 1990 andDolder, 2002) and for bees (Peng et al, 1993, Zama et al, 2001, Zama et al, 2004, Zama et al, 2005a, Zama et al, 2005b, Báo et al, 2004and Fiorillo et al, 2005. The presence of four acrosomal vesicle lateral projections along the perforatorium is not observed in other Hymenoptera already examined.…”
Section: Discussionmentioning
confidence: 99%